Tuberculosis transmission by patients with smear-negative pulmonary tuberculosis in a large cohort in the Netherlands - Tostmann, Alma; Kik, Sandra V; Kalisvaart, Nico A; Sebek, Maruschka M; Verver, Suzanne; Boeree, Martin J; van Soolingen, Dick (Clinical infectious diseases, 2008)
Sputum smear microscopy is commonly used for diagnosing tuberculosis (TB). Although patients with sputum smear-negative TB are less infectious than patients with smear-positive TB, they also contribute to TB transmission. The objective of this study was to determine the proportion of TB transmission events caused by patients with smear-negative pulmonary TB in The Netherlands. All patients in The Netherlands with culture-confirmed TB during the period 1996-2004 were included in this study. Patients with identical DNA fingerprints in Mycobacterium tuberculosis isolates from sputum samples were clustered. The first patients in a cluster were considered to be the index patients; all other patients were considered to have secondary cases. In addition, we examined transmission from sources by conventional contact tracing. We analyzed 394 clusters with a total of 1285 patients. On the basis of molecular linkage only, 12.6% of the secondary cases were attributable to transmission from a patient with smear-negative TB. The relative transmission rate among patients with smear-negative TB, compared with patients with smear-positive TB, was 0.24 (95% confidence interval, 0.20-0.30). Secondary cases in clusters with an index patient with smear-negative TB more frequently had smear-negative status (odds ratio, 1.86; 95% confidence interval, 1.18-2.93), compared with secondary cases in clusters with an index patient with smear-positive TB. Conventional contact tracing revealed that 26 (6.2%) of the 417 sources, as identified by the Municipal Health Services, had smear-negative TB. In The Netherlands, patients with smear-negative, culture-positive TB are responsible for 13% of TB transmission. Countries that have ample resources should expand their TB-control efforts to include prevention of transmission from patients with smear-negative, culture-positive pulmonary TB.